52 Advanced T lymphocyte analysis system (ATLAS) for in-depth immunological interrogation in real-world conditions, a methodological strategy. (9th November 2020) - Berg, Stephanie; Joyce, Cara; Reyes, Michael Delos; Burke, Brianna; Plaza-Rojas, Lourdes; Prajapati, Kushal; Perez, Cynthia; Wagner, Courtney; Elliott, Elizabeth; Knox, Blaine; Linden, Daniel; Clark, Joseph; et al.
Abstract : Background: Humans are genetically diverse and possess a rich immunological history. It is logical to consider that these factors may lead to differences in individual immunological responses to therapy when diagnosed with cancer. The successful implementation of immune-based therapies against cancer has brought the need to develop strategies to create meaningful profiles that faithfully depict the patient's immunological status. We report an in-depth immunological interrogation methodology, termed ATLAS. This system was designed to generate an accurate representation of the patient's immunological landscape that can be used during various time points during immune-checkpoint inhibitor (ICI) therapy. Methods: We selected data from our prospective registry trial at Loyola University Medical Center to design individual immunological profiles of patients diagnosed with locally advanced or metastatic solid tumors planning to receive ICI. Only metastatic melanoma patients samples pre-ICI therapy are included in this first analysis. Twenty mL of peripheral blood were collected. Giving consideration to scientific rigor and limited sample availability, the assays were designed in miniaturized forms. ATLAS includes classical peripheral blood mononuclear cells (PBMCs) composition and T cell phenotypic and transcriptional analysis. To depict T cell functionality, we examined multiple parameters such as T cell receptor (TCR) signaling threshold, cell proliferation and NF-kB activation, at steady-state and in response to cell activation. To obtain both a broad and T cell-specific view, we quantified circulating chemokines and cytokines in plasma and from activated T cells. Results: For this first methodologic demonstration, patient characteristics are depicted in table 1. Data from different ATLAS assays were used to create individual immunological profiles presented as a dashboard for each patient. Distributional plots and measures of center (mean, median) and spread (range, variance) were used to eliminate low-information parameters from the figures. Data visualizations compared individual patients to the sample median for continuous parameters and compared patients' percentages to sample average relative abundance. Two patients, P011 shown in figure 1 and P021 shown in figure 2, are depicted using this approach. Conclusions: ATLAS can be used in real-world conditions to generate comprehensive immunological profiles of cancer patients. Individual profiles indicate that immunological constitution is heterogeneous among patients, even with the same tumor type. We propose that the addition of ATLAS to our clinical and immunological toolbox may help stratify patients to articulate truly personalized oncologic therapies. Ethics Approval: The study was approved by Loyola University Medical Center and Loyola University Chicago Ethics Board and Institutional Review Board, approval number 209364.